Observation on the morphological and gonadal aspects of Cladonema radiatum (Class: Hydrozoa) from Tuticorin Bay, Southeast coast of India - Ranjith, L.; Kalidas, C.; Saravanan, R.; Jagadis, I.; Prabu, D. Linga; Kavitha, M.; Babu, A. Mathan; Joshi, K.k.; Manojkumar, P.p. (Zootaxa, 2021)
Studies on the hydrozoan fauna (Phylum: Cnidaria; Class: Hydrozoa) of the Indian waters during the 20th century were few in number (Nagale and Apte, 2013a, b). They originated in the early 1900s (Annandale, 1907; Ritchie, 1910, Thornely, 1916, Gravely, 1927), focussing on the taxonomy of hydroids in the 1960s along the southern coast, including Lakshadweep and Andaman Islands (Mammen, 1963, 1965a, b) and in the 1980s along the northern coast (Venugopalan & Wagh, 1986). Species of the hydrozoan family Cladonematidae (Anthoathecata; Capitata) include benthic, creeping and swimming hydroids comprising four genera viz., Cladonema, Eleutheria, Staurocladia and the nomen dubium Dendronema (Schuchert, 2021). Cladonema differs from other genera of Cladonematidae by the branched tentacles either with an adhesive structure or cnidocytes and having nematocysts in oral knobs (Ghory et al., 2020 & Farias et al., 2020). The taxonomy of Cladonema is uncertain and species in the genus have undergone several rounds of grouping and splitting. Gershwin & Zeidler (2008) gave a detailed account of 13 putative species of Cladonema. However, Schuchert (2021) considered six species to be valid viz., C. radiatum, C. californicum, C. myersi, C. novaezelandiae, C. pacificum and C. timmsii. Studies on the genus Cladonema from Indian waters are patchy, with a brief report of its occurrence among other hydroids (Sastry and Chandramohan, 1989; Santhakumari and Nair, 1999; Arun et al., 2018). Among these records from India, C. myersi was collected from an experimental aquarium with seawater from an unknown location (Prasad, 1961). The present study documents the occurrence and describes the morphology and gonadal features of Cladonema radiatum from Tuticorin Bay, Gulf of Mannar, Southeast coast of India.